Resistensi Perempuan Pemain Valorant terhadap Ketimpangan Gender di Ruang Siber - Weluz, Theodore Abelardo (Peneliti.net, 2025)
Advances in technology and a growing number of internet users have transformed social interactions, particularly in online gaming environments like Valorant. While these games aim to create inclusive spaces, gender inequality often persists due to stereotypes and traditional gender roles that extend into virtual communities. This research analyzes the experiences of female players in the Valorant Indonesia Community (VIC) regarding gender inequality and their subsequent resistance to discrimination. The study addresses two main questions: (1) what forms of gender inequality do female Valorant players encounter in cyberspace, and (2) how do these women resist such inequalities? The findings reveal that female players in VIC frequently face negative stereotypes, verbal harassment, marginalization, and subordination. In response to these challenges, they exhibit resistance through open acts such as voicing injustices and forming supportive women's groups, as well as covert strategies like maintaining privacy and adapting to less welcoming environments. This resistance aligns with the principles of liberal feminism, reflecting their efforts to achieve equality in cyberspace. Ultimately, the study underscores the necessity for more inclusive measures to foster a safer and more equitable gaming atmosphere free from gender-based discrimination.